Transcriptomic profile of premature ovarian insufficiency with RNA-sequencing - Wu, Jiaman; Feng, Shiyu; Luo, Yan; Ning, Yan; Qiu, Pingping; Lin, Yanting; Ma, Fei; Zhuo, Yuanyuan (Frontiers in Cell and Developmental Biology, 2024)
Background: This study aimed to explore the transcriptomic profile of premature ovarian insufficiency (POI) by investigating alterations in gene expression. Methods: A total of sixty-one women, comprising 31 individuals with POI in the POI group and 30 healthy women in the control group (HC group), aged between 24 and 40 years, were recruited for this study. The transcriptomic profiles of peripheral blood samples from all study subjects were analyzed using RNA-sequencing. Results: The results revealed 39 differentially expressed genes in individuals with POI compared to healthy controls, with 10 up-regulated and 29 down-regulated genes. Correlation analysis highlighted the relationship between the expression of SLC25A39, CNIH3, and PDZK1IP1 and hormone levels. Additionally, an effective classification model was developed using SLC25A39, CNIH3, PDZK1IP1, SHISA4, and LOC389834. Functional enrichment analysis demonstrated the involvement of these differentially expressed genes in the "haptoglobin-hemoglobin complex," while KEGG pathway analysis indicated their participation in the "Proteoglycans in cancer" pathway.The identified genes could play a crucial role in characterizing the genetic foundation of POI, potentially serving as valuable biomarkers for enhancing disease classification accuracy.